Apoptosis, Dysbiosis and Expression of Inflammatory Cytokines are Sequential Events in the Development of 5‐Fluorouracil‐Induced Intestinal Mucositis in Mice. Issue 3 (10th May 2017) - Hamouda, Nahla; Sano, Tatsushi; Oikawa, Yosuke; Ozaki, Toru; Shimakawa, Masaki; Matsumoto, Kenjiro; Amagase, Kikuko; Higuchi, Kazuhide; Kato, Shinichi
Abstract: The chemotherapeutic agent 5‐fluorouracil (5‐FU) causes intestinal mucositis with severe diarrhoea, but the pathogenesis is not fully understood. In this study, we investigated the pathogenic effects of 5‐FU in mice, focusing on apoptosis, enterobacteria and inflammatory cytokines. Repeated administration of 5‐FU caused severe intestinal mucositis on day 6, accompanied by diarrhoea and body‐weight loss. TNF‐α expression increased 1 day after exposure to the drug, and spiked a second time on day 4, at which point myeloperoxidase activity and IL‐1β expression also increased. Apoptotic cells were observed in intestinal crypts only on day 1. 5‐FU also induced dysbiosis, notably decreasing the abundance of intestinal Firmicutes while increasing the abundance of Bacteroidetes and Verrucomicrobia . Twice‐daily co‐administration of oral antibiotics significantly reduced the severity of intestinal mucositis and dysbiosis, and blocked the increase in myeloperoxidase activity and cytokine expression on day 6, without affecting apoptosis and TNF‐α up‐regulation on day 1. In cultured colonic epithelial cells, exposure to 5‐FU also up‐regulated TNF‐α expression. Collectively, the data suggest that crypt apoptosis, dysbiosis and expression of inflammatory cytokines are sequential events in the development of intestinal mucositis after exposure to 5‐FU. In particular, 5‐FU appears to directly induce apoptosis via TNF‐α and to suppress intestinal cell proliferation, thereby resulting in degradation of the epithelial barrier, as well as in secondary inflammation mediated by inflammatory cytokines.